Assessing the Using Salt and Activated Carbon in the Cleaning of Biogas in Households in Mukono District - Joram Kalumba (Uganda Christian University, 2024)
The research study focuses on cleaning and purification before its efficient utilization by people in households in Mukono district. The purification process involves removing impurities like carbon dioxide and hydrogen sulphide to improve the quality of the biogas analyzing and highlighting their cost efficiency to the local people in households. The research aims at assessing the use of salt and activated carbon to clean and purify the biogas in households of people in Mukono district. Analysis of biogas is done before and after cleaning and purifying the gas. The salt is mixed with water to form a saline acting adsorbent to remove carbon dioxide and activated carbon acts as the purifier used to remove hydrogen sulphide to improve the quality of the being produced in households. A cleaning biogas unit is designed and fabricated for household users in Mukono district.